Impact evaluation of insecticide resistance management strategies in cotton under Technology Mini-Mission on Cotton (Gossypium hirsutum) - KUMAR, RISHI; MONGA, D; JAT, S L; INDORIA, A K; CHAUHAN, R; KRANTHI, K R (The Indian Journal of Agricultural Sciences, 2012)
A location specific Insecticide Resistance Management (IRM) strategies module developed for pest management in Bt and Non Bt cotton was implemented and evaluated in cotton (Gossypium hirsutum) growing villages of Haryana .Large scale field evaluation of the technology indicated the reduction in number of insecticidal sprays (30.65%, 24.29% in 2007–08 and 2008–09, respectively) and shift in pesticide use pattern in adopted villages. Though the populations of sucking pests were not significantly different in IRM and Non IRM fields but total consumption of insecticides was 26.79% and 31.24% higher during 2007–08 and 2008–09, respectively in Non-IRM over IRM villages. Moreover, IRM adopted villages of Sirsa, Fatehabad and Hisar harboured higher number of natural enemies as compared to non IRM villages. The yield was found significantly higher in fields where IRM strategies were adopted (21.60 and 23.79 q/ha) over field that adopted farmers practices (i e non IRM) (20.74 and 21.61 q/ha) during 2007–08 and 2008–09.